Iowa’s Annual Phosphorus Budget: Quantifying the Inputs and Outputs of Phosphorus Transport Processes - Elliot Anderson; Keith Schilling; Christopher Jones; Larry Weber; Calvin Wolter (Land)
Phosphorus (P) plays an integral part in Iowa’s economic and environmental activities through its role as an essential nutrient and waterborne pollutant. However, the amount of phosphorus transported through these activities has not been well quantified. This study estimates the annual mass of P entering and exiting Iowa’s landscape from 1998 to 2022 through seven transport pathways. Four input pathways (fertilizer application, manure production, industrial sources, and human sources) and three output pathways (harvesting, livestock grazing, and stream export) were quantified using various agricultural, economic, and water quality datasets. We also estimated the total mass of P present in the top 0.61 m layer of Iowa’s landscape using results from a statewide soil sampling survey. The harvest component was the largest, with annual values consistently above 200 million kg. This was followed by the fertilizer and manure components, with annual values near 100 million kg. The other components were much smaller; the mean grazing and stream export values were 15 and 19 million kg, respectively, and human and industrial sources were less than 4 million kg. Stream export was the most dynamic pathway, with the largest coefficient of variation (0.59). The net P budget (inputs–outputs) was negative in 20 of the 25 years assessed, indicating that Iowa typically runs a P deficit. A trend analysis revealed that the manure, human, industry, and harvesting components increased across the 1998–2022 period while the grazing component decreased. The mass of P in Iowa’s top layer of soil was 81.5 billion kg—orders of magnitude larger than any individual budget component. This analysis provides a new perspective on P transport pathways in Iowa and may help inform policymakers as they make decisions on the many activities involving P.